Land-use and climate related drivers of change in the reindeer management system in Finland: Geography of perceptions - Rasmus, Sirpa; Wallen, Henri; Turunen, Minna; Landauer, Mia; Tahkola, Juho; Jokinen, Mikko; Laaksonen, Sauli
2021